Identifikasi Penyakit Pada Kambing Menggunakan Metode Fuzzy Tsukamoto - Zaiful Bahar; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Goatshare one source of animal protein that is in demand by Indonesian people after cattle and chickens. However, disease in goats is an important thing that must be considered, because it can cause harm to farmers and can even cause livestock deaths. The problem of recognizing the symptoms of goat disease can be solved by using the system. So a system was made to identify diseases in goats, so that farmers could find out the types of diseases that attacked and handled them appropriately. The method used is fuzzy tsukamoto. Fuzzy Tsukamoto method is one method that can be used to process the value of symptom input to identify disease. The initial step of this method includes the value of the symptom of the disease. Then do fuzzification calculations, inference calculations and defuzzification calculations. Based on the results of the tests that have been carried out in this study, the accuracy of the 50 test data is 94%.